KEKUASAAN SIMBOLIK DALAM WACANA POLITIK DI MEDIA CETAK - Wahyuni, Lilik (Universitas Muhammadiyah Surakarta, 2008)
As a social practice, language is used to persuade, influence, argue, refuse, maintain, and to response oneâs reaction. Using language, one may practically pro- duce and reproduce authority. This article deals with the symbolic fight and the mechanism of symbolic force within politics discourse in written media. The analy- sis technique used is critical discourse analysis, especially in the interaction be- tween language and social structure. The result shows that the symbolic fight in the written media represents the practice of continuing the doxa by the orthodoxa group and of attacking it by the heterodoxa group. The strategies of fighting the doxa are by showing the orthodoxa groupâs weaknesses, arousing the enmity within the group, comparing the orthodoxa group to others, and by using SARA and com- munity issues. The mechanism of the symbolic force used by the ortodoxa is the use of euphemism and censor.Â Key words: kekuasaan simbolik, doxa, orthodoxa, SARA, dan wacana politik.Â Â Â